State of the Art and Contribution to the Documentation on Fishing, Aquaculture and on the Microbiological Profile of Clarias Gariepinus and Oreochromis Niloticus Two Species of Fish Reared in the Whedos of the Upper Ouémé Delta in the Republic of Benin - Radji, Kafilath; Glodjinon, Nicéphore M.; Ohin, Brice A.M.; Tovide, Noël S.; Noumavo, Pacôme A.; Baba-Moussa, Lamine; Baba-Moussa, Farid (European Scientific Journal, ESJ, 2023)
Fish is an important source of animal protein in Africa and is used in the composition of several national dishes. This literature review examines fishing, aquaculture and fish reared in the whèdos of the upper Ouémé delta in Benin. It addresses socio-economic aspects, nutritional importance and traditional fish preservation technology. The sources of information used are publications, books, reports of dissertations and theses and technical notes. It was found that Clarias gariepinus and Oreochromis niloticus, among others, are two species of fish most often raised in the whèdos of the Ouémé River in Benin. These fish adapt to large variations of ecological factors of the aquatic environment found everywhere in Africa and reproduce easily in captivity, which favors their breeding in ponds. These species present multiple fish farming qualities: resistance to high densities, resistance to diseases and low oxygen levels, easy adaptation to artificial feeding and high growth. Microbiological contamination of fish flesh occurs only after capture and can be endogenous or exogenous contamination. Generally, several processes are used to overcome this problem of contamination of fish. Hot smoking and drying are very often used. The lack of hygiene in the traditional technology of smoking fish sometimes favor a considerable microbial contamination of the obtained products. Thus, contaminated fish can be the cause of foodborne diseases such as food poisoning. Most of the pathogenic strains responsible for these diseases are resistant to certain antibiotics.